Polityka pieniężna Narodowego Banku Polskiego w latach 2000-2009 - Szarek, Ewelina (My University, 2011)
Weryfikacja przyjętej w pracy hipotezy nastąpiła poprzez porównanie osiągniętych przez NBP wyników z wyznaczonymi celami inflacyjnymi. W 2000 roku nie udało się zrealizować wytyczonego celu. Rada Polityki Pieniężnej swoje krótkookresowe cele osiągnęła w 2001 r., 2002 r. oraz 2003 r. W drugim z badanych kwartałów, zakładany cel inflacyjny nie został osiągnięty pomiędzy czerwcem 2004 a lipcem 2005 roku. W trzecim kwartale, tj. od 2007 do 2009 roku poziom inflacji mieścił się w przyjętych granicach przedziału wahań, w okresach: styczeń – lipiec 2007 r., w grudniu 2008 r. oraz w 7 z 12 miesięcy 2009 roku. Inflacja na koniec roku wynosiła odpowiednio w 2007 - 4%, 2008 - 3,3%, 2009 - 3,5% i tylko w jednym roku, z wymienionych lat, pozostawała powyżej górnej granicy wahań. Rezultatem pracy jest pozytywna opinia działania NBP pomimo, iż w niektórych z badanych lat założone cele nie zostały osiągnięte.

A verification of the hypothesis adopted in the work was made through comparing the results achieved by NBP to its designated inflation targets. Year 2000 did not bring success in attaining the defined goal. The Monetary Policy Council achieved its short-term objectives in years 2001, 2002, and 2003. In the second quarter, out of those under the study, the assumed inflation target was not achieved between June 2004 and July 2005. In the third quarter, i.e. from 2007 to 2009, inflation was within accepted fluctuation limits, in the periods: January - July 2007, in December 2008 and in seven out of twelve months in 2009. At the end of the year, inflation was respectively, in 2007 - 4%, 2008 - 3.3%, 2009 - 3.5% and only in one of the enumerated years it remained above the upper limit of fluctuation. The work results in a positive evaluation of NBP operations, despite the fact that in some of the years under the study the designated goals were not achieved.
The monetary policy of the National Bank of Poland in 2000-2009 year
Keywords: Narodowy Bank Polski; polityka pieniężna; instrumenty polityki pieniężnej; inflacja; National Bank of Poland; monetary policy; monetary policy instruments; inflation